2016
DOI: 10.1007/s00253-016-7755-6
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial properties and death-inducing mechanisms of saccharomycin, a biocide secreted by Saccharomyces cerevisiae

Abstract: We recently found that Saccharomyces cerevisiae (strain CCMI 885) secretes antimicrobial peptides (AMPs) derived from the glycolytic enzyme glyceraldehyde 3-phosphate dehydrogenase (GAPDH) that are active against various wine-related yeast and bacteria. Here, we show that several other S. cerevisiae strains also secrete natural biocide fractions during alcoholic fermentation, although at different levels, which correlates with the antagonistic effect exerted against non-Saccharomyces yeasts. We, therefore, ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 42 publications
6
55
0
Order By: Relevance
“…The other mechanism i.e., the cross inhibition between LAB and yeast, might be occurred. LAB produced lactic acid potentially inhibit yeast growth (Narendranath et al, 2001) or saccharomycin secreted by S. cerevisiae can inhibit bacteria (Branco et al 2017). In contrast, mutual interaction between LAB and yeast could be found at sourdough (Sieuwerts et al, 2018) or Kefir (Stadie et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The other mechanism i.e., the cross inhibition between LAB and yeast, might be occurred. LAB produced lactic acid potentially inhibit yeast growth (Narendranath et al, 2001) or saccharomycin secreted by S. cerevisiae can inhibit bacteria (Branco et al 2017). In contrast, mutual interaction between LAB and yeast could be found at sourdough (Sieuwerts et al, 2018) or Kefir (Stadie et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As presented in Table 1, co-fermentations of non-Saccharomyces yeast strains and S. cerevisiae contained lower concentrations of ethanol (9.74%-10.24%) and total acidity (7.68-8.63 g/L) than pure S. cerevisiae fermentation did (11.29% and 9.44 g/L). The Sc-Hu co-fermentation possessed a lower concentration of residual sugar (1.38 g/L), while others contained a higher level of residual sugar (2.03-2.81 g/L) than pure S. cerevisiae fermentation did (2.03 g/L), which might be caused by different sugar consumption abilities of these yeast strains [30,31]. The pH value of co-fermentations (3.37-3.47) increased compared with that of pure S. cerevisiae fermentation (3.35), which was also found in co-fermented bilberry wine [32].…”
Section: Physicochemical Parameters Of Citrus Winementioning
confidence: 95%
“…Posteriorly, the authors studied the antifungal action mechanism of the characterized peptides, demonstrating that they produce disruption in the cell wall integrity in H. guilliermondii [50]. Finally, when synthetic isoforms of this AMP were produced, it was observed that they are not as effective as natural peptides [51]. By assessing the biochemical characteristics of AMPs and their antifungal action mechanisms, it can be said that the use of antimicrobial peptides for biocontrol of spoilage yeasts in the winemaking industry could be an effective tool.…”
Section: Antimicrobial Peptides As a Contaminant Bio-control Tool In mentioning
confidence: 99%
“…The antifungal capacity was quantified by measuring the diameter of the inhibition halo generated around C. intermedia LAMAP1790 (represented with red dotted lines). Left to right columns: S. cerevisiae BY4741, S. cerevisiae EC1118, B. bruxellensis LAMAP1359, B. bruxellensis LAMAP2480, B. bruxellensis LAMAP3276, and B. bruxellensis LAMAP3294[51].…”
mentioning
confidence: 99%